The technological and institutional change in the Port wine industry: a long-run perspective - Jacquinet, Marc (2003)
In the present paper, I will proceed to the study of a particular sector, the Port wine industry, which is geographically well defined and historically significant. The interesting point is the historical evidence which goes back to the sixteenth century (and even further), but we will concentrate on the last three centuries for they give us an exemplary case to discuss the relevance of institutions and technological and legal factors in the shaping of the production techniques used and the structure and organization of the sector.